2021
DOI: 10.3389/fmicb.2020.549254
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Multidrug-Resistant Escherichia coli BH100 Sub-strains

Abstract: The rapid emergence of multidrug-resistant (MDR) bacteria is a global health problem. Mobile genetic elements like conjugative plasmids, transposons, and integrons are the major players in spreading resistance genes in uropathogenic Escherichia coli (UPEC) pathotype. The E. coli BH100 strain was isolated from the urinary tract of a Brazilian woman in 1974. This strain presents two plasmids carrying MDR cassettes, pBH100, and pAp, with conjugative and mobilization properties, respectively. However, its transpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Although the plasmid of strain SD/21-15 had no AMR-genes in its genome, other A. media isolates had plasmids having various AMR genes that included bla KPC-1 , bla OXA-427 , sul1, bla OXA-1 , and qnr genes. In additions, the detected plasmids had several transposases, such as Tn3, ISAs1, IS1595, and IS4 known to carry various AMR-gene cassettes (Dziewit et al, 2012;Baquero et al, 2013;Carvalho et al, 2021). The plasmids also encoded various efflux pump proteins, such as tet(E), merD, mexC, OprJ, mph(E), (Chopra, 2002), and mph(A) known to play significant roles in drug trafficking across cell membranes (Dayao et al, 2016;Kim et al, 2017;Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although the plasmid of strain SD/21-15 had no AMR-genes in its genome, other A. media isolates had plasmids having various AMR genes that included bla KPC-1 , bla OXA-427 , sul1, bla OXA-1 , and qnr genes. In additions, the detected plasmids had several transposases, such as Tn3, ISAs1, IS1595, and IS4 known to carry various AMR-gene cassettes (Dziewit et al, 2012;Baquero et al, 2013;Carvalho et al, 2021). The plasmids also encoded various efflux pump proteins, such as tet(E), merD, mexC, OprJ, mph(E), (Chopra, 2002), and mph(A) known to play significant roles in drug trafficking across cell membranes (Dayao et al, 2016;Kim et al, 2017;Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This strain was obtained from the urinary tract of a Brazilian woman in 1974, but was not fully described until now. The usage of the Next Generation Sequencing (NGS) technique allowed assessing the entire sequence of the genome of the strain and it was found that the bacterium harbors two plasmids carrying MDR cassettes: pBH100 and pAp, presenting conjugative and mobilization properties, respectively [ 80 ]. The authors indicated transposon Tn 21 as the one likely responsible for the mobilization of the streptomycin resistance gene— aadA (encoding for streptomycin 3′-adenylyltransferase).…”
Section: Mobile Genetic Elements In Antibiotic Resistancementioning
confidence: 99%
“…Carvalho et al [ 80 ] also described the Tn 3 transposon, associated with the bla TEM gene, which encodes the β-lactamase TEM-1 type enzyme. Members of the Tn 3 transposon family form a widespread and homogeneous group of bacterial TEs that play a major role in disseminating antibiotic resistance.…”
Section: Mobile Genetic Elements In Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…IS elements are usually formed by one or two genes delimited by two TIRs. Interestingly, many ISs contain promoter sequences that can modify the expression of neighboring genes 22 24 , and several families have been associated with the dissemination of antibiotic resistance and the spread of multidrug-resistance 9 , 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%